2017
DOI: 10.1186/s12876-017-0681-y
|View full text |Cite
|
Sign up to set email alerts
|

Trends in prevalence, mortality, health care utilization and health care costs of Swiss IBD patients: a claims data based study of the years 2010, 2012 and 2014

Abstract: BackgroundReal-life data on inflammatory bowel disease (IBD) prevalence and costs are scarce. The aims of this study were to provide an overview of the prevalence, mortality, health care utilization and costs of IBD patients in Switzerland in the years 2010, 2012, and 2014.MethodsBased on claims data of the Helsana-Group, prevalence of IBD was assessed for 2010, 2012 and 2014. Mortality rates, costs (inpatient, outpatient, medication costs) and utilization (visits, hospitalizations) were compared between patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 59 publications
1
29
0
3
Order By: Relevance
“…We observed that 8.22 % of all IBD patients received a therapy with a biologic agent. This number is much smaller than in previous studies addressing countries other than Germany, such as France (12 %) [14], Switzerland (12.8 %) [15], or the United States (11 %) [16], but it is in line with previous German studies (UC: 2.5 -3.2 %; CD: 8.2 -8.4 %) [17,18]. We cannot evaluate whether our identified low biologics quota documents an under-treatment of IBD patients with these agents, as neither the disease activity was coded in our claims data nor systemic CS prescriptions in patients not receiving biologics were assessed.…”
Section: Discussionmentioning
confidence: 55%
“…We observed that 8.22 % of all IBD patients received a therapy with a biologic agent. This number is much smaller than in previous studies addressing countries other than Germany, such as France (12 %) [14], Switzerland (12.8 %) [15], or the United States (11 %) [16], but it is in line with previous German studies (UC: 2.5 -3.2 %; CD: 8.2 -8.4 %) [17,18]. We cannot evaluate whether our identified low biologics quota documents an under-treatment of IBD patients with these agents, as neither the disease activity was coded in our claims data nor systemic CS prescriptions in patients not receiving biologics were assessed.…”
Section: Discussionmentioning
confidence: 55%
“…Allergic asthma affects 9.5% of children and adolescents in the United States (Akinbami et al, 2012). People with asthma can develop comorbidities with other atopic disorders and other health outcomes (Guerra et al, 2004; Lødrup Carlsen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In brief, unit costs for IBD-related inpatient and outpatient events recorded in the SIBDCS were estimated from reimbursement claims data obtained from the Helsana Group (see Supplementary Files Table S8 for a full list of procedures considered). This is a leading health insurance company in Switzerland providing statutory health insurance to 15% of the population 4 . Costs estimated from this dataset are based on national reimbursement tariffs, which are standardised across Switzerland (TARMED 28 in the outpatient sector and Swiss diagnosis-related groups 29 in the inpatient sector) and adjust for regional variations in costs.…”
Section: Direct and Indirect Costsmentioning
confidence: 99%
“…In Switzerland, uptake of novel biologic treatments was associated with a marked increase in health care expenditures placing significant financial pressure on the health system 3 . The changing treatment landscape and a rising prevalence 4 mark an important opportunity to identify clinically-and cost-efficient treatment strategies.…”
mentioning
confidence: 99%